FDR and the Spanish Civil War : neutrality and commitment in the struggle that divided America - Tierney, Dominic, 1977- (e-Duke books scholarly collection., 2007)
Provides new understanding of Franklin Roosevelt's involvement in the Spanish Civil War, claiming that he was activist and pro-Loyalist.